Moderator teams: an extension to focus group methodology - Prince, Mel; Davies, Mark (Qualitative Market Research: An International Journal, 2001)
Traditional focus group methodology involves an individual trained moderator who manages the whole process from writing the focus group guide that directs the topics pursued, the interaction with participants, to interpretation, reporting and client feedback. Since their training, personality and orientation can vary differentially, this may lead to moderator bias. Proposes a new method that involves a series of complementary moderators that target specific areas of the guide that allows them to specialise in their particular experiences and orientations. These moderators are used sequentially on the same groups that offer the potential to avoid many of the problems associated with single-moderator discussion groups. Moreover, the chance to moderate the moderator keeps a check on how the sessions of each focus group develops, building in feedback between moderators, and reduces the prospects of misinterpretation and side-tracking by a single moderator. © 2001, MCB UP Limited
Keywords: Equal value; Focus groups; Management; dept.mkt